Learning from young children : research in early childhood music - Burton, Suzanne L. (Suzanne Louise); Taggart, Cynthia Crump, 1957- (Rowman & Littlefield Education, 2011)
In early childhood, the most important period of learning and human development, young children often achieve developmental milestones in a short time. Learning from Young Children: Research in Early Childhood Music presents research on the importance of fostering musical growth during this period. These studies discuss: · applying brain research to young children's musical growth · music in the home and child-care contexts · musical characteristics of the young child · language acquisition as a lens on music learning · music as a foundation for communication · parental conceptions of the role.